Efektivitas Penggunaan Media Flashcard terhadap Aktivitas Belajar Siswa Kelas III Mata Pelajaran IPAS - Riska Rahmawati; Fitria Nurulaeni (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study was motivated by low student learning activity in the Natural and Social Sciences (IPAS) subject, resulting from a teacher-centered instructional approach that limited optimal student participation. The study aimed to analyze the effectiveness of using flashcards on the learning activity of third-grade students at SDN Lembursitu during the 2025/2026 academic year. A quantitative approach was employed using an experimental method and a “True Experimental Design” (specifically, a Pretest-Posttest Control Group Design). The sample consisted of 30 students divided into experimental and control groups. Data were collected through questionnaires, observation, and documentation, and subsequently analyzed using tests for validity, reliability, normality, and homogeneity, alongside descriptive analysis, the Independent Sample T-Test, and the N-Gain test. The results indicated that the instrument was valid and reliable, with a Cronbach’s Alpha value of 0,763. The experimental group achieved an average learning activity score of 49,33 (82,22%), classified as “very high,” while the control group scored 42,67 (71,11%), classified as “high”. Hypothesis testing yielded a significance value of 0,012 (<0,05). Furthermore, the average N-Gain score for the experimental group was 65,93% (moderately effective), whereas the control group scored 37,82% (less effective). These findings demonstrate that the use of flashcard is more effective than conventional instruction in enhancing student learning activity in the IPAS subject.